Treatment of trichloroethylene contaminated wastewater using Fenton’s reagent - Tiyarattanachai, Ronnachai; Kanatharana, , Proespichaya; Neng Hsieh, Hsin- (Malaysian Journal of Science, 2004)
The treatment of trichloroethylene (TCE) was carried by using the Fenton’s reagent. The study was conducted by optimization of Fenton’s reagent, H202 and Fe2+, and TCE ratio. Effect of Ti02 addition and the recycling of iron and Ti02 sludge were also studied. The economic was evaluated base on the treatment efficiency at the optimum conditions and ratio of initial substances. The results showed that the optimum molar concentration ratio of H202: Fe2+: TCE was 20:2:1. The Ti02 added to the systems that conducted by this work insignificantly enhance treatment efficiency. The results of recycling of the reagents showed promising result.